Pengaruh Etos Kerja, Gaya Kepemimpinan, Dan Reward Terhadap Kinerja Pegawai Dinas Perpustakaan Dan Kearsipan Kabupaten Seluma - Sita Paramita; Ida Anggriani; Bahman Effendi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This research is motivated by the importance of improving employee performance at the Seluma Regency Library and Archives Service in providing optimal public services, one of which is influenced by internal and external factors such as work ethic, leadership style, and the reward system implemented. This study aims to examine the influence of work ethic, leadership style, and rewards on employee performance at the Library and Archives Office of Seluma Regency. This research is quantitative in nature, using questionnaires and analysis methods. The population in this study consists of all employees of the Library and Archives Office of Seluma Regency, totaling 35 people, with the sampling technique using a census sampling method. Data were collected through questionnaires and then analyzed using validity and reliability tests, multiple linear regression, coefficient of determination, and hypothesis testing with the assistance of SPSS 24 software. The results of the multiple regression testing all showed an increase from a value of 0, meaning there is a positive and direct relationship from the coefficients of work ethic (X1), leadership style (X2), and reward (X3). The t-test results showed that Work Ethic (X1) had a t-count of 2.472 > t-table 1.692 and a significance of 0.019 < 0.05, the Leadership Style (X2) test showed t-count 2.064 > t-table 1.692 and significance 0.047 < 0.05, and the Reward (X3) test showed t-count 2.054 > t-table 1.692 and significance 0.048 < 0.05. Based on the comparison of the F-count value with the F-table value, the F-count is greater than the F-table value, namely 4.452 > 2.660; therefore, it is concluded that the hypothesis is accepted, meaning there is a simultaneous effect of Work Ethic (X1), Leadership Style, and Reward (X3) on the performance (Y) of employees at the Seluma Regency Library and Archives Office. This is evident from the significance level of 0.010 < 0.05. Thus, work ethic, leadership style, and rewards have a positive and significant effect on employee performance, both partially and simultaneously.